2012
DOI: 10.1634/theoncologist.2012-0274
|View full text |Cite
|
Sign up to set email alerts
|

Genetically Engineered Cancer Models, But Not Xenografts, Faithfully Predict Anticancer Drug Exposure in Melanoma Tumors

Abstract: Background. Rodent studies are a vital step in the development of novel anticancer therapeutics and are used in pharmacokinetic (PK), toxicology, and efficacy studies. Traditionally, anticancer drug development has relied on xenograft implantation of human cancer cell lines in immunocompromised mice for efficacy screening of a candidate compound. The usefulness of xenograft models for efficacy testing, however, has been questioned, whereas genetically engineered mouse models (GEMMs) and orthotopic syngeneic tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 23 publications
0
37
0
Order By: Relevance
“…Recent studies have shown that the PK of carboplatin in genetically engineered mouse models (GEMMs) of melanoma more closely resembles the tumor disposition of carboplatin seen in patient with cutaneous tumors when compared to other transplanted melanoma tumor models (Combest et al 2012). The combination of the results from the study by Combest et al (2012), and our current study suggest that flank tumor models may not be optimal to evaluate the tumor delivery and efficacy of CMAs. However, the comparison of the tumor delivery of CMAs and SMs in several types of tumors models and in patients with solid tumors needs to be performed to confirm these results.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that the PK of carboplatin in genetically engineered mouse models (GEMMs) of melanoma more closely resembles the tumor disposition of carboplatin seen in patient with cutaneous tumors when compared to other transplanted melanoma tumor models (Combest et al 2012). The combination of the results from the study by Combest et al (2012), and our current study suggest that flank tumor models may not be optimal to evaluate the tumor delivery and efficacy of CMAs. However, the comparison of the tumor delivery of CMAs and SMs in several types of tumors models and in patients with solid tumors needs to be performed to confirm these results.…”
Section: Discussionmentioning
confidence: 99%
“…33,34 Notwithstanding the above criticisms, GEMMs may have advantages over xenograft models in their cellular composition and/or sensitivity to therapeutic agents. 48 Specifically, GEMM tumors contain stromal and hematopoietic components not possible in a human tumor xenograft setting, and thus these tumors may respond more appropriately to small molecules, immunomodulatory, and/or biological agents that cross-react with mouse antigens. Nevertheless, for the various reasons outlined above, GEMMs will likely provide limited insight into oncogenesis and patient tumor heterogeneity.…”
Section: Traditional Models Have Not Predicted Clinical Successmentioning
confidence: 99%
“…Genetically engineered mouse (GEM) models result in spontaneously growing tumors as opposed to induced; that is they begin growing from a small number of mutated cells and thus may more accurately represent the natural development of D. Ling et al tumors. In fact, preliminary studies seem to suggest they are more predictive of clinical outcomes than their xenograft counterparts [183]. Thus we wanted to grow both a spontaneous GEM mammary tumor and a 1 × 10 6 -cell induced mammary tumor in the same mouse.…”
Section: Conclusion and Prospectivesmentioning
confidence: 99%